Efektivitas 3 spesies lebah madu sebagai agen polinasi untuk meningkatkan produktivitas (>40%) biji jarak pagar (Jatropha curcas) pada ekosistem iklim basah - . Kasno; A.E. Zainal Hasan; Dedi Sholeh Efendi; . Syaefuddin (Institut Pertanian Bogor, 2010)
The physic nut (Jatropha curcas) is one of potential plant for producing biodiesel, however efforts to socialization have still encounter constraints. The production system so far has not come to a level of attractive to the fellow farmers due to low productivity. Therefore further researches on production system are still urgently needed. This research entitled